2021
DOI: 10.1161/atvbaha.120.316063
|View full text |Cite
|
Sign up to set email alerts
|

Low LAL (Lysosomal Acid Lipase) Expression by Smooth Muscle Cells Relative to Macrophages as a Mechanism for Arterial Foam Cell Formation

Abstract: Objective: We previously reported smooth muscle cells (SMCs) represent ≥50% of foam cells in human coronary and ≈70% in apoE (apolipoprotein E)-deficient mouse aortic atheromas and exhibit reduced expression of the cholesterol exporter ABCA1 (ATP-binding cassette transporter A1). A major stimulus for ABCA1 expression is flux of cholesterol out of lysosomes, generated by hydrolysis of lipoprotein cholesteryl esters by LAL (lysosomal acid lipase). In this study, we investigated the potential role lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 55 publications
5
46
0
Order By: Relevance
“…3,[43][44][45] In contrast, agLDL loading of VSMCs results in lysosomal trapping of agLDL-associated cholesterol, with these cells remaining devoid of established LDs and failing to upregulate ABCA1. 12,42 several studies have shown VSMC conversion to foam cells following incubation with mβ-CD-cholesterol complexes, with mβ-CD-cholesterol-derived cholesterol bypassing initial lysosome lipoprotein processing and allowing for their conversion to foam cells. 14,15,26 VSMC conversion to foam cells is accompanied by loss of expression of VSMC markers and acquisition of expression of macrophage markers.…”
Section: Discussionmentioning
confidence: 99%
“…3,[43][44][45] In contrast, agLDL loading of VSMCs results in lysosomal trapping of agLDL-associated cholesterol, with these cells remaining devoid of established LDs and failing to upregulate ABCA1. 12,42 several studies have shown VSMC conversion to foam cells following incubation with mβ-CD-cholesterol complexes, with mβ-CD-cholesterol-derived cholesterol bypassing initial lysosome lipoprotein processing and allowing for their conversion to foam cells. 14,15,26 VSMC conversion to foam cells is accompanied by loss of expression of VSMC markers and acquisition of expression of macrophage markers.…”
Section: Discussionmentioning
confidence: 99%
“…A major study from the Francis group revealed that in human coronary artery sections, at least 50% of total intimal foam cells were derived from VSMCs and that about 40% of CD68+ cells were of VSMC rather than myeloid origin [ 103 ]. They also showed that the gene expressions of the cholesterol exporter protein ATP-Binding Cassette A1 (ABCA1) and lysosomal acid lipase (LAL), a cytosolic enzyme which hydrolyzes cholesteryl esters (the main form of cholesterol storage) to free cholesterol, were significantly reduced in VSMC-foam cells but not in macrophages-foam cells, suggesting that VSMCs may contain a much larger burden of lipids than macrophages, as they are unable to release excess lipid via ABCA1 and LAL [ 103 , 104 ]. In line with this observation, a study found that TNF ligand-related molecule 1A (TL1A), a vascular endothelial growth inhibitor reducing neovascularization, was able to inhibit the development of atherosclerosis by regulating VSMC (but not macrophage) foam cell formation by activating ABCA1, ABCG1 and cholesterol efflux by a liver X Receptor (LXR)-dependent signaling pathway [ 105 ].…”
Section: Vascular Smooth Muscle Cells and Early Atherosclerosismentioning
confidence: 99%
“…However, VSMC-derived foam cells lack the cellular machinery to properly efflux accumulated cholesterol. For instance VSMCs have reduced expression of ABCA1 [ 215 , 290 ], and low expression of lysosomal acid lipase (LAL) [ 104 ] compared with macrophages. As a result, increasing ABCA1 and LAL expression in foam cells (especially in VSMCs) seems to be a promising therapeutic strategy to reduce atherosclerotic plaque burden.…”
Section: Promising Macrophage and Vsmc Targeting Therapeutic Strategiesmentioning
confidence: 99%
“…Interestingly, the level of the soluble LDL receptor-related protein 1 in the circulating blood is increased in patients with coronary artery disease ( 92 , 93 ). When compared with cultured human macrophages, cultured human SMCs express relatively low levels of LAL ( 94 ). Accordingly, in SMC foam cells, the ingested neutral lipids tend to accumulate within lysosomes, while in macrophages they appear as cytosolic droplets.…”
Section: Introductionmentioning
confidence: 99%